2015
DOI: 10.3126/kumj.v11i2.12485
|View full text |Cite
|
Sign up to set email alerts
|

Fluoride Concentration in Community Water and Bottled Drinking Water: A Dilemma Today

Abstract: Background

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…This result was similar with a study done in bottled water in Mathura City and Faridabad City in India. 22,23 A study done in Chennai also had less than optimal fluoride content in bottled water and there was a significant variation in fluoride concentration of each brand and among different batches of same brand bottled waters. 24 In another study done by Armfield et al, has clearly shown that the consumption of non-public water (bottled water and rainwater tanks) may put the children at increased risk of developing caries.…”
Section: Discussionmentioning
confidence: 99%
“…This result was similar with a study done in bottled water in Mathura City and Faridabad City in India. 22,23 A study done in Chennai also had less than optimal fluoride content in bottled water and there was a significant variation in fluoride concentration of each brand and among different batches of same brand bottled waters. 24 In another study done by Armfield et al, has clearly shown that the consumption of non-public water (bottled water and rainwater tanks) may put the children at increased risk of developing caries.…”
Section: Discussionmentioning
confidence: 99%
“…The permissible limit as given by Bureau of Indian Standards (BIS) and World Health Organization (WHO) is 0.6-1.2 mg/l and 1.5 mg/l respectively for fluoride in drinking water. International studies support the widely held view that the majority of bottled waters available contain negligible fluoride in terms of its dental health benefits (3). The total annual bottled water consumption in India had tripled to 5 billion liters in 2004 from 1.5 billion liters in 1999.the global consumption of bottled water was nearly 200 billion liters in 2006 (4).…”
mentioning
confidence: 94%